2008
DOI: 10.1152/ajpheart.00880.2008
|View full text |Cite
|
Sign up to set email alerts
|

Newborn resuscitation: should we oxygenate or not?

Abstract: HOW SHOULD WE OXYGENATE newborn and infants suffering from hypoxia and ischemia? Is it harmful to use 100% O 2 ? It may seem odd to question a practice that has been carried out for so long, seemingly without any adverse effects. The case is, however, that after the practice of routinely using 100% O 2 for newborn resuscitation was examined, many serious potentially harmful effects have to date been described (for review, see Ref. 13).Fabian et al.(1) add new information to the topic of how asphyxiated newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Ultimately, this leads to hypoxic-ischemic injury as a result of inadequate oxygen supply to the brain tissue. As result, brain tissue oxygen tension would be increased (38). In our current experiment, the results suggested that locomotor activity of mice were gradually improved in Normabaric hyperoxia treated animals as compared to injured animals without treatment.…”
Section: Discussionsupporting
confidence: 51%
“…Ultimately, this leads to hypoxic-ischemic injury as a result of inadequate oxygen supply to the brain tissue. As result, brain tissue oxygen tension would be increased (38). In our current experiment, the results suggested that locomotor activity of mice were gradually improved in Normabaric hyperoxia treated animals as compared to injured animals without treatment.…”
Section: Discussionsupporting
confidence: 51%